New record of the genus Leucinodella Strand from Laos (Lepidoptera, Crambidae, Spilomelinae), with description of a new species - Ko, Jae-Ho; Bayarsaikhan, Ulziijargal; Lee, Tak-Gi; Cha, Yeong-Bin; Kim, Han-Ul; Park, Bo-Sun; Kwon, Hyung Wook; Bae, Yang-Seop (Zootaxa, 2020)
The genus Leucinodella Strand (1918) is reported from Laos for the first time, with a new species, Leucinodella banthaensis n. sp., and one newly recorded species, Leucinodella leucostola (Hampson, 1896). A key to Leucinodella species in Laos is provided, with illustrations of adults and genitalia.